Selenium in the Treatment of Graves’ Hyperthyroidism and Eye Disease - Lanzolla, Giulia; Marinò, Michele; Marcocci, Claudio (Frontiers in Endocrinology, 2021)
Based on the role of oxidative stress in the pathogenesis of Graves’ hyperthyroidism (GH) and Graves’ Orbitopathy (GO), a therapy with the antioxidant agent selenium has been proposed and a number of studies have been performed, both in vitro and in vivo. In GH, reactive oxygen species (ROS) contribute to the thyroid and peripheral tissues damage. In GO, tissue hypoxia, as well as ROS, are involved in the typical changes that occur in fibroadipose orbital tissue and the perimysium of extraocular muscles. Antioxidants have been proposed to improve the effects of antithyroid drugs in GH patients, as well as the remodeling of orbital tissues in patients with GO. A randomized clinical trial on the use of selenium in patients with mild GO provided evidence for a beneficial effect; no data are available on more severe forms of GO. Although the real effectiveness of selenium in patients with GH remains questionable, its use in the management of mild GO is generally believed to be beneficial, and selenium administration has been included in the clinical practice for the patients with mild eye disease.